DEVELOPMENT OF A NATURAL LABORATORY MODEL BASED ON LOCAL WISDOM TO ENHANCE DISASTER LITERACY - Asari, Ruli; Fadjarajani, Siti; Badriah, Liah; Nurjamilah, Ai Siti; Shaari, Mohammad Zohir Bin Ahmad (Universitas Sebelas Maret (UNS), 2025)
This study presents a natural laboratory model based on local wisdom to improve disaster literacy, drawing on the indigenous knowledge of Kampung Naga and Kampung Kuta in West Java, Indonesia. By integrating traditional disaster mitigation practices, such as Ngasuh Lembur and Sedekah Bumi, with modern tools like Geographic Information Systems (GIS), the research offers a culturally tailored disaster education framework. The model, tested by 120 Geography Education students at Universitas Siliwangi, demonstrated a 32% improvement in students' understanding of disaster risks. The synergy between cultural traditions and modern techniques fostered stronger engagement and deeper retention of disaster preparedness knowledge. Feedback highlighted the importance of balancing cultural authenticity with technological innovation, leading to refinements that enhanced both relevance and effectiveness. This study addresses a critical gap in disaster education by offering a sustainable, adaptable framework that bridges local wisdom and formal education, making it applicable across diverse cultural and environmental settings globally.